Cases in medical microbiology and infectious diseases - Gilligan, Peter H. , 1951-; Miller, Melissa Blair , 1972-; Shapiro, Daniel S. , 1959- (ASM Press, 2014)
This book challenges students to develop a working knowledge of the variety of microorganisms that cause infections in humans. This valuable, interactive text will help them better understand the clinical importance of the basic science concepts presented in medical microbiology or infectious disease courses.